2020
DOI: 10.1186/s12920-020-00752-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial GWAS and association of nuclear – mitochondrial epistasis with BMI in T1DM patients

Abstract: Background: BMI is a strong indicator of complications from type I diabetes, especially under intensive treatment. Methods: We have genotyped 435 type 1 diabetics using Illumina Infinium Omni Express Exome-8 v1.4 arrays and performed mitoGWAS on BMI. We identified additive interactions between mitochondrial and nuclear variants in genes associated with mitochondrial functioning MitoCarta2.0 and confirmed and refined the results on external cohorts: the Framingham Heart Study (FHS) and GTEx data. Linear mixed m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Moreover, genetic variants in nuclear genes could lead to oxidative disorders or modulate the mitochondrial variants [ 81 ], and mild nuclear gene variants could potentially become clinically relevant when combined with an incompatible MT DNA [ 92 ]. Additive interactions (epistasis) between mitochondrial variants in the MT-ND2 gene and nuclear variants in genes responsible for mitochondrial replication and transcription have been demonstrated to influence the BMI and obesity phenotype [ 93 ]. Similarly, our previous investigations have demonstrated the role of nuclear-encoded mitochondria imported genes in coordinating the response to hypercholesterolemia and atherosclerotic lesion expansion, as well as foam cell formation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genetic variants in nuclear genes could lead to oxidative disorders or modulate the mitochondrial variants [ 81 ], and mild nuclear gene variants could potentially become clinically relevant when combined with an incompatible MT DNA [ 92 ]. Additive interactions (epistasis) between mitochondrial variants in the MT-ND2 gene and nuclear variants in genes responsible for mitochondrial replication and transcription have been demonstrated to influence the BMI and obesity phenotype [ 93 ]. Similarly, our previous investigations have demonstrated the role of nuclear-encoded mitochondria imported genes in coordinating the response to hypercholesterolemia and atherosclerotic lesion expansion, as well as foam cell formation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions involving mtDNA haplogroups are not new. Different studies revealed mito-nuclear genetic interactions that modulate the effect of specific nuclear genetic variants on the risk of Alzheimer 26 , Parkinson 27 , multiple sclerosis 28 or increased BMI in patients with type I Diabetes mellitus 29 . In addition, mitochondrial variation also influences the DNA methylome of articular chondrocytes 30 as well as global methylation levels in peripheral blood DNA 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genetic variants in nuclear genes could lead to oxidative disorders or modulate the mitochondrial variants [81] and mild nuclear gene variants could potentially become clinically relevant when combined with an incompatible MT DNA [105]. Additive interactions (epistasis) between mitochondrial variants in MT-ND2 gene and nuclear variants in genes responsible for mitochondrial replication and transcription have been demonstrated to influence the BMI and obesity phenotype [66]. Similarly, our previous investigations have demonstrated the role of nuclear encoded mitochondria imported genes in coordinating the response to hypercholesterolemia and atherosclerotic lesion expansion, and foam cell formation [102].…”
Section: Discussionmentioning
confidence: 99%